Association between Ambient Air Pollution Exposure and Ocular Surface Disorders Among Adults in Urban Lahore. A Cross-Sectional Clinical Study - ABBAS, IRUM; KITCHLEW, ZYIEMAH ARIF; RAHIM, SUMAIRA; RIAZ, KASHIF (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Urban air pollution has turned out to be a leading issue of public health in Lahore with frequent air smog cases, contributing to a high level of ocular morbidity. Pollutants of the air particularly affect the eyes because the eyes constantly encounter the environment. Objectives: It is aimed to determine the correlation between the exposure to air pollution in the ambient setting and ocular surface diseases among adults living in Lahore. Methods: It was a cross-sectional clinical study in 100 adults who were recruited at ophthalmology outpatient clinics. The structured questionnaires and clinical examinations, which were used to get the data included tear break-up time (TBUT), Schirmer test, eyelid margin test, conjunctival hyperemia, allergic conjunctivitis, and meibomian gland dysfunction. The level of exposure was determined with the help of outdoor time per day, living in close relation to traffic and industrial facilities, and environmental AQI. Results: Eye redness (72%), dryness (68%), burning sensation (61%), tearing (54%) and foreign-body sensation (49%) were found to be the most common. Clinically diagnosed dry eye (TBUT <10 seconds) was found in 58% of the subjects, low tear production in 40% and meibomian gland dysfunction in 32%. The percentage of allergic conjunctivitis was detected as 27. The exposure to greater pollution levels was associated with greater ocular symptoms and lower tear stability. Conclusion: There are several ocular surface disorders that have a close correlation with ambient air pollution among the adult population in Lahore. There is an urgent need to implement preventive methods such as the development of public awareness, protection-based eyewear, and prompt ophthalmic examination during smog-prone instances to decrease the morbidity of the eye in a highly polluted environment.